2020
DOI: 10.1177/0890334420909815
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Reimbursement Cost of Human-Milk-Based Neonatal Therapy in Polish Health Care Service

Abstract: Background A human-milk-based diet is the best option for nutritional therapy for preterm and/or sick newborns. Research aim The study aims were to restructure the reimbursement rates to hospitals in Poland for infants’ tube feedings to favor the use of donor human milk over formula for newborns who required supplementation of expressed mother’s milk and evaluate the results of the financing change during the first year of implementation (2018). Methods Financial data from hospitals were collected (2015–2016) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The largest percentage was off the overweight reason due to the growth of the fetus and hormonal changes in the body, which led to an increase in the size of the breast and uterus and an increase in the volume of blood and amniotic fluid. A difference between these findings can only be attributable to those studies conducted by Wesołowska in Poland:(43%) for BMI (25-29.5) kg/2m,18% for BMI (25 -29.9) kg/2m and(39%) for BMI (30-39.9) kg/2m (15) .The current results demonstrated that based on a questionnaire about dietary supplements, the highest percentage of supplement use was according to recommendations( 49.2%) by family to use nutritional supplements. According to their experiences and beliefs (40.8), E. Luay, S. H. Almukhtar P J M H S Vol.…”
Section: Discussionmentioning
confidence: 70%
“…The largest percentage was off the overweight reason due to the growth of the fetus and hormonal changes in the body, which led to an increase in the size of the breast and uterus and an increase in the volume of blood and amniotic fluid. A difference between these findings can only be attributable to those studies conducted by Wesołowska in Poland:(43%) for BMI (25-29.5) kg/2m,18% for BMI (25 -29.9) kg/2m and(39%) for BMI (30-39.9) kg/2m (15) .The current results demonstrated that based on a questionnaire about dietary supplements, the highest percentage of supplement use was according to recommendations( 49.2%) by family to use nutritional supplements. According to their experiences and beliefs (40.8), E. Luay, S. H. Almukhtar P J M H S Vol.…”
Section: Discussionmentioning
confidence: 70%
“…Our data revealed that a third party payer reimburses those costs for the procurement of DHM in only three out of 10 countries (France, Austria, and Poland). However, actual costs may only be partially refunded to the facility responsible for milk bank operations (Wesolowska et al, 2020). Since we demonstrated that the overwhelming majority of European HMBs are operated by neonatal departments, our data indicate that the respective health care facility covers the costs of its DHM services and for establishing HM banks.…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that a third party payer reimburses those costs for the procurement of DHM in only three out of 10 countries (France, Austria, and Poland). However, actual costs may only be partially refunded to the facility responsible for milk bank operations (Wesolowska et al, 2020). Since participating countries compared to the potential number of eligible infants.…”
Section: Reimbursement Of Milk Bank Operationsmentioning
confidence: 99%
“…Die fehlende Kostenerstattung der Bereitstellung von Frauenmilch spiegelt sich in europäischen Nachbarländern wider 12 . Nach einer aktuellen Erhebung erfolgt eine anteilige Kostenerstattung nur in drei europäischen Ländern, entweder abhängig von der Zahl der versorgten Neugeborenen oder von der generierten Menge Frauenmilch 5 .…”
Section: Finanzierung Der Frauenmilchbereitstellungunclassified